SOSIAL BUDAYA MASYARAKAT JAWA DI KECAMATAN TANJUNG EMAS, KABUPATEN TANAH DATAR, SUMATERA BARAT - Salsabilla Wilda Alifia; Retnaningtyas Susanti; Agusti Efi; Elida Elida (IJTIMAIYAH Jurnal Ilmu Sosial dan Budaya, 2025)
This article discusses the socio-cultural dynamics of the Javanese community in Tanjung Emas District, Tanah Datar Regency, West Sumatra, in the context of adaptation and acculturation with the Minangkabau community. This study reveals how the Javanese community, as a transmigration population, has succeeded in maintaining ancestral traditions such as kenduri, slametan, and wedding customs, while adopting local cultural elements, such as the use of Minangkabau traditional clothing and the tradition of kenduri adat. This cultural harmony is seen in strong social relations through mutual cooperation, mixed marriages, and cross-cultural interactions. This article also shows the role of Javanese associations in strengthening relations between communities and the younger generation who are able to balance Javanese cultural identity with openness to Minangkabau culture. With an observational approach and in-depth interviews, this article emphasizes the importance of tolerance and openness in creating cultural synergy that enriches the diversity of traditions in Indonesia.